Ergothioneine, a dietary antioxidant improves amyloid beta clearance in the neuroretina of a mouse model of Alzheimer’s disease - Wijesinghe, Printha; Whitmore, Clayton A.; Campbell, Matthew; Li, Charles; Tsuyuki, Miranda; To, Eleanor; Haynes, Justin; Pham, Wellington; Matsubara, Joanne A. (Frontiers in Neuroscience, 2023)
Ergothioneine (Ergo) is a naturally occurring dietary antioxidant. Ergo uptake is dependent on the transporter, organic cation transporter novel-type 1 (OCTN1) distribution. OCTN1 is highly expressed in blood cells (myeloid lineage cells), brain and ocular tissues that are likely predisposed to oxidative stress. Ergo may protect the brain and eye against oxidative damage and inflammation, however the underlying mechanism remains unclear. Amyloid-beta (Aβ) clearance is a complex process mediated by various systems and cell types including vascular transport across the blood–brain barrier, glymphatic drainage, and engulfment and degradation by resident microglia and infiltrating innate immune cells. Impaired Aβ clearance is a major cause for Alzheimer’s disease (AD). Here we investigated neuroretinas to explore the neuroprotective effect of Ergo in a transgenic AD mouse model. Age-matched groups of Ergo-treated 5XFAD, non-treated 5XFAD and C57BL/6J wildtype (WT controls) were used to assess Ergo transporter OCTN1 expression and Aβ load along with microglia/ macrophage (IBA1) and astrocyte (GFAP) markers in wholemount neuroretinas (n = 26) and eye cross-sections (n = 18). Immunoreactivity was quantified by fluorescence or by semi-quantitative assessments. OCTN1 immunoreactivity was significantly low in the eye cross-sections of Ergo-treated and non-treated 5XFAD vs. WT controls. Strong Aβ labeling, detected in the superficial layers in the wholemounts of Ergo-treated 5XFAD vs. non-treated 5XFAD reflects the existence of an effective Aβ clearance system. This was supported by imaging of cross-sections where Aβ immunoreactivity was significantly low in the neuroretina of Ergo-treated 5XFAD vs. non-treated 5XFAD. Moreover, semi-quantitative analysis in wholemounts identified a significantly reduced number of large Aβ deposits or plaques, and a significantly increased number of IBA1(+)ve blood-derived phagocytic macrophages in Ergo-treated 5XFAD vs. non-treated 5XFAD. In sum, enhanced Aβ clearance in Ergo-treated 5XFAD suggests that Ergo uptake may promote Aβ clearance possibly by blood-derived phagocytic macrophages and via perivascular drainage.